Land bank as a strategic asset of agribusiness under the functioning of the land market - Olkhovsky, Volodymyr (Здобутки економіки: перспективи та інновації, 2026)
Given wartime challenges, structural transformations in the agricultural sector, and the development of new mechanisms of land circulation, particular importance is attached to assessing the role of the land bank in ensuring production activities, investment attractiveness, and the long-term sustainability of enterprises. The purpose of the study is to determine the economic essence of the agribusiness land bank and to assess current trends in its formation under the functioning of the agricultural land market in Ukraine. The study employs methods of scientific generalization and systematization to reveal the economic content of the land bank; statistical analysis to assess land market dynamics, land values, and regional characteristics of land circulation; comparative analysis to examine the structure of land transactions; graphical and tabular methods to visualize the research results; and logical synthesis to identify strategic opportunities and risks associated with the development of agribusiness land assets. The research results indicate that, under the functioning of the agricultural land market, the land bank is increasingly acquiring the characteristics of a strategic agribusiness asset that simultaneously supports production activities, enhances the investment attractiveness of enterprises, and contributes to their capitalization. The development of the land market during 2021–2025 was characterized by the recovery of business activity following a decline in land transactions due to wartime events, an increase in land values, and the gradual strengthening of the role of purchase-and-sale transactions within the structure of land dealings. Significant regional differentiation was identified in both land values and the intensity of land bank formation, with security conditions emerging as a key influencing factor. The highest concentration of land acquisitions was observed in regions with strong agricultural potential and relatively stable business environments. The systematization of strategic opportunities and risks demonstrated that the further development of the land market creates prerequisites for land consolidation, improved land-use efficiency, and enhanced financial sustainability of agribusiness enterprises, while simultaneously increasing the influence of wartime, investment, and regulatory risks on the formation of land assets.